Probability Distribution and Determination of Blast Loading during Structural Blast Resistant Study - Taochun Yang; Yaozhi Luo; Guangqing Hu; Yi Jiang (Shock and Vibration)
Explosion overpressure and its duration are important parameters describing blast loading. However, their values obtained using the currently available methods differ significantly. To address this problem, we simulated the overpressure reflection coefficient (i.e., the ratio of reflection overpressure to incident overpressure) and fitted the analytical expressions to the test data. We then collected a large amount of theoretical and experimental blast loading data from literature and studied the probability distribution of blast loading for different scaled distances. The results show that the probability density function of explosion overpressure obeys an exponential distribution when the scaled distance is between 0.1  m/kg1/3 and 0.5  m/kg1/3. On the other hand, it obeys a normal distribution when the scaled distance is greater than 0.5  m/kg1/3. The coefficient of variation reaches the maximum value of 1 when the scaled distance is between 0.1  m/kg1/3 and 0.5  m/kg1/3, while it is between 0.13 and 0.2 when the scaled distance is from 1.5  m/kg1/3 to 6  m/kg1/3. The coefficient of variation of reflected overpressure is slightly bigger than that of incident overpressure. Nevertheless, the coefficient of variation of proportional duration (i.e., the ratio of actual duration to cubic root of charge mass) is generally smaller, between 0.408 and 1.017. It was also found that there is no clear probability distribution for the blast loading duration. Finally, formulas for the explosion overpressure and proportional duration were determined together with their 95% confidence level bounds.